1987
DOI: 10.1073/pnas.84.10.3434
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide I stimulates insulin gene expression and increases cyclic AMP levels in a rat islet cell line.

Abstract: Insulin secretion is controlled by a complex set of factors. Although blood glucose levels serve as the major stimulus of insulin secretion in mammals, insulin release is also modulated by amino acids, catecholamines, glucagon, and other, intestinal hormones. The identification of factors that modulate insulin production has engendered much interest because of their potential importance in the altered dynamics of insulin secretion in response to glucose characteristic of maturity-onset diabetes mellitus. Decod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
542
2
11

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 783 publications
(567 citation statements)
references
References 32 publications
12
542
2
11
Order By: Relevance
“…In addition, the increased early response of insulin secretion during the GTT in liraglutide-treated mice is in line with the working mechanism of GLP-1 [25,26]. This was associated with a major reduction in beta cell mass in both control and HFD-fed mice.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, the increased early response of insulin secretion during the GTT in liraglutide-treated mice is in line with the working mechanism of GLP-1 [25,26]. This was associated with a major reduction in beta cell mass in both control and HFD-fed mice.…”
Section: Discussionsupporting
confidence: 67%
“…function, such as Pdx-1, Glut2, glucokinase, and insulin (12)(13)(14)(15)(16), and by providing protection against apoptosis (17). Recently we have also demonstrated that an important site of GLP-1 action is on the hepatoportal glucose sensor.…”
Section: Gluco-incretins Control Insulin Secretion At Multiple Levelsmentioning
confidence: 99%
“…GLP-1 exerts its multiple biological effects through binding of its specific G-protein-coupled receptor, GLP1R. GLP1R is mainly expressed by pancreatic β-cells, and activation of this receptor in response to ligand stimulation increases the intracellular cAMP level, leading to stimulation of insulin secretion by two different pathways, PKA-dependent and PKA-independent exchange protein directly activated by cAMP (EPAC) pathways (Drucker et al, 1987;Fehmann et al, 1995). Subsequently, PKA and EPAC increase protein phosphorylation and intracellular Ca 2+ concentration (Kieffer et al, 1999), causing increased synthesis and secretion of insulin by β-cells.…”
Section: Introductionmentioning
confidence: 99%